2022
DOI: 10.1186/s12889-022-12908-4
|View full text |Cite
|
Sign up to set email alerts
|

Considering intermittent fasting among Saudis: insights into practices

Abstract: Background There is a dearth of studies on intermittent fasting in Saudi Arabia outside of Ramadan. The aim of this research was to study and describe the practice of intermittent fasting outside of Ramadan among Saudi people. Methods A web-based survey that focused on intermittent fasting practices—specifically the use of intermittent fasting applications, goal setting, and the effects of fasting on an individual’s state of health—was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The findings of our study showed that the number of males was slightly higher than the females by 7.4%, while another study has shown that female participants tend to be a majority, and also practice IF longer than males [1]. When it comes to age category, most of our respondents were between the age of 18 and 35, which makes sense since this age group is adolescents/adults who have greater concern about their weight than any other age category.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The findings of our study showed that the number of males was slightly higher than the females by 7.4%, while another study has shown that female participants tend to be a majority, and also practice IF longer than males [1]. When it comes to age category, most of our respondents were between the age of 18 and 35, which makes sense since this age group is adolescents/adults who have greater concern about their weight than any other age category.…”
Section: Discussionmentioning
confidence: 44%
“…Fasting is a practice followed by our ancestors for thousands of years; it has several aspects and is of different types such as for religious, cultural, or health reasons. Muslims fast during the month of Ramadan for a specific period during the day, which is similar to intermittent fasting (IF) [1]. This type of diet is based on an eating pattern that alternates between periods of fasting and eating.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we explore lifestyle habits as well as health perceptions among a sample of Spanish adults following an IF diet to better understand the practice of this dietary approach. IF, as a highly intriguing clinical nutritional approach, is more and more recognized in our society not only for its health benefits [22,[41][42][43] but also for the convenience of practicing it [44,45]. A growing popularity has been noticed as well as an increasing interest among the Spanish population, decreasing the interest in the Mediterranean diet [46].…”
Section: Discussionmentioning
confidence: 99%
“…This fact leads to an imbalance between the number of men and women who reported following an IF diet, with 783 women (76.92%) out of the total 1018 IF practitioners in our sample. This gender distribution may reflect either a heightened interest among women in diet interventions [17] or that men are less likely to participate in surveys [22,42,47]. An exception is presented in a study conducted on the Saudi population, which showed a slightly higher participation of men compared to women [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation